Managing Dissent: Institutional Culture and Political Independence in the South African Broadcasting Corporation's News and Current Affairs Division - Arndt, C (Department of Political Studies, 2024)
Despite a fairly successful institutional transformation in the early 1990s, the South African Broadcasting Corporation (SABC), in particular its News and Current Affairs division, is widely perceived to lack political independence from the African National Congress-led government and to have neglected its role as a political watchdog in South Africa's young democracy. Most academic studies continue to be concerned with formal factors such as the SABC's institutional structure, media laws, or commercial imperatives -yet have not been able to explain the above anomaly. This paper focuses instead on the institutional culture around editorial independence which is conceptualised as comprising of beliefs (journalists' role perceptions), values (news values and the professional ethos) and internal practices (news decision-making, internal debate etc.). The main focus of analysis lies on the ways dissent is being managed within the corporation. This paper transcends the classical boundaries of political science into the neighbouring disciplines of media studies and sociology and draws specifically on (a) the literature on public broadcasting in young democracies, (b) debates around journalists' roles and professional values, and ( c) conceptualisations of institutional culture as well as power and power relations within organisations. In-depth interviews with 17 current and former SABC employees suggest that beliefs and values around editorial independence are highly contested at the SABC - in particular among staff and management and so much so that the struggle around which ones should be dominant has become part of the institutional culture itself. The resulting dissent is being managed both from above (by management and senior editors) and from below (by newsroom staff). The SABC does not seem to be subject to unusual levels of political pressure from outside. Instead, threats to editorial independence seem to originate mostly on the level of the SABC's board and senior news management. They take the form of pressure and rewards which, in combination, effectively stifle independent thinking and hence work against editorial independence and a professional ethos integral to the SABC's public broadcasting mandate. Hirschman's concepts of exit, voice, and loyalty are used to analyse how journalists respond to such pressure and rewards. While exit is not an option for many staff and voice is perceived as costly, loyalty (towards the idea of public broadcasting) does not appear to be very common either. Instead, what I call opportunistic loyalty or quiescence in the face of power seems to be the preferred way of dealing with the dilemma of individually-held values and beliefs and a dominant institutional culture that runs contrary to them. As a result debate is silenced, staff morale suffers and routine processes of news decision-making are easily manipulated by senior managers or other powerful individuals with the will to enforce their preferred values and beliefs (which in tum might have little to do with the ideals of public broadcasting). Journalists and editors seem to generally be reluctant to get involved in sensitive news decisions, to take responsibility and exercise their professional judgement which then makes the corporation potentially vulnerable to political interference from outside as well.